Horizons Already Here: Video Games and Landscape. - Murray, Soraya (Art Journal)
The article explores the aesthetic, art historical and visual studies perspectives of video game development. Research on representation in video games to be presented at a College Art Association (CAA) Annual Conference is discussed, including the term gamescapes coined by Shoshana Magnet in which landscape in video games is ideologically constructed and an examination of the simulated terrains of games that reflect the aspects of the lived world by geography scholar Michael W. Longan.